A review of microalgal cell wall composition and degradation to enhance the recovery of biomolecules for biofuel production - Md Nadzir, Syafiqah; Yusof, Norjan; Nordin, Norazela; Kamari, Azlan; Yusoff, Mohd Zulkhairi Mohd (Taylor & Francis, 2023)
Microalgal biomass has received much attention as a renewable energy source and a possible replacement for petroleum-based fuels. Currently, mechanical, thermal, and chemical cell disruption methods are limited in terms of economics, sustainability, and environmental friendliness. Because of this, biological methods are preferred. The structure and composition of cell walls in commonly used commercial microalgae, as well as the production of lipid and carbohydrate biomolecules for microalgal biofuel, are discussed in this paper. Furthermore, the advantages and disadvantages of various mechanical and non-mechanical cell disruption methods for recovering biomolecules from microalgae are compared. The current biological methods of cell disruption are investigated, such as gene manipulation and autolysis. The relationship between autolysis and programmed cell death and factors influencing the process are also discussed. This review will help researchers select the proper method for recovering biomolecules from microalgae. The findings should expand the use of autolytic biological approaches for economic cell disruption in biofuel commercialisation.